Characteristics of theravada sangha bikkhu robes in Indonesia - Damana, I ketut (Institute of Computer Science (IOCS), 2024)
The aim of developing the characteristics of bhikhu s angha t heravada in Indonesia This arises from the issue of big beliefs that arise from the noble nature of robes in society, addressing the causes of the use of parikkhar a robes as a characteristic of the robes trend. Thank you Angha t heravada has different colors. This type of secondary data comes from data obtained indirectly from objects through interviews, as well as primary data obtained from in-depth interviews. The author did this by using a qualitative descriptive method by collecting data related to the object of research regarding the characteristics of robes. The data presentation model is a structured collection of information that provides the possibility of drawing conclusions and taking action Miles and Huberman. The result is cloth cut into pieces with a tendency to weave to form the pattern of Magadha's rice fields. Its character function is to protect the body from insect bites. Finally, the author hopes that this research can make a contribution to school institutions.